Release and migration of Pb from Pb(ii) and Pb(iv) compounds in the presence of microbiological activity. Issue 12 (12th October 2022) - Gao, Yaohuan; Trueman, Benjamin F.; Li, Bofu; Earle, Martin R.; Gagnon, Graham A.
Abstract : Periodic detachment of biofilm or dynamics of biological activity may not be reflected by spikes in Pb release. Abstract : Microorganisms were allowed to inhabit flow-through systems containing representative Pb corrosion products, Pb(iv ) oxide and Pb(ii ) carbonate. Local tap water was fed to the system. After 277 days of operation, distinct microbial communities were developed on the two Pb compound surfaces and both differed from those on the filter media of a full-scale biofilter, which served as the inoculum. A large proportion of the microorganisms were heavy-metal tolerant. Pyromorphite-like compounds were detected in all solid samples at the end, except for the Pb(iv ) control with minimal biological activity. Pb release to the tap water increased in the test groups as compared to the controls. In continuous flow mode, fractionation of Pb in the tap water leaving the flow-through systems (the effluent) showed that most Pb was in the filtrates passing the sterile filters (0.2 μm) (Pb[ii ], 73.8%; Pb[iv ], 64.4%). Besides, the filtrates during ATP quantification, with most microbial cells intercepted (0.22 μm), contained 64.6 ± 13.5% (Pb[ii ]) and 67.7 ± 21.6% (Pb[iv ]) of the total effluent Pb. During stagnation tests, the filtrates in ATP quantification generally contained over 50% of the total Pb in the first 60 ml effluent upon water resumption. These results indicate that most of the soluble and some colloidal Pb did not co-migrate with microbial cells once released to tap water, although microbial cells and biofilm debris usually carry negative charges. Additionally, the variation of the dissolved organic carbon (DOC) did not correlate with the variation of the increased Pb or ATP in the tap water effluent. The level of planktonic microorganisms in the effluent, as reflected by ATP, did not correlate with Pb release in the Pb(ii ) system while a weak correlation was observed in the Pb(iv ) system. Since potential residue from the inoculum and inorganic content in tap water may complicate the Pb dissolution in the presence of biofilms, future studies are required to illustrate the interactions among these components. Overall, this study suggests that physiochemical Pb dissolution may be complicated by biological instability in distribution systems due to heavy-metal tolerant microorganisms that grow on Pb scales.